2012
DOI: 10.1021/jp306392e
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer and Photoluminescence Intermittency of Single Emitters in Dyed Crystals

Abstract: The role of proton transfer in the photoluminescence intermittency (PI) of single molecules of violamine R (VR) overgrown in potassium acid phthalate (KAP) crystals is evaluated in comparisons of protonated (KAP) and deuterated (DKAP) mixed crystals between 23 and 60 °C. The PI is analyzed by the construction of cumulative distribution functions that are statistically compared. We find that the on- and off-interval duration distributions change with isotopic substitution consistent with proton transfer contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 53 publications
4
32
2
Order By: Relevance
“…Although power-law behavior is often reported in blinking studies 8,9,26 and has been reported for delayed luminescence as well, 1,4,5 deviations from power-law have been emphasized in recent blinking literature. [27][28][29] Deviations from power-law kinetics are clearly evident in the delayed luminescence kinetics reported here. For both delayed luminescence (this study) and some blinking data, [27][28][29] log-normal distributions reproduce the dynamics better than power-law distributions.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although power-law behavior is often reported in blinking studies 8,9,26 and has been reported for delayed luminescence as well, 1,4,5 deviations from power-law have been emphasized in recent blinking literature. [27][28][29] Deviations from power-law kinetics are clearly evident in the delayed luminescence kinetics reported here. For both delayed luminescence (this study) and some blinking data, [27][28][29] log-normal distributions reproduce the dynamics better than power-law distributions.…”
Section: Discussionmentioning
confidence: 56%
“…[27][28][29] Deviations from power-law kinetics are clearly evident in the delayed luminescence kinetics reported here. For both delayed luminescence (this study) and some blinking data, [27][28][29] log-normal distributions reproduce the dynamics better than power-law distributions. Even more compelling is the observation in blinking measurements on CdSe NCs that the "off" statistics (which reflect detrapping dynamics analogous to the delayed luminescence decay dynamics described here) are also temperature independent, 8,9,26,30,31 implying a tunneling process for detrapping.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, the PI exhibited by VR in KAP and DKAP was analyzed using new statistical methods [ 56 ] to determine if the underling probability distribution functions describing the on - and off -durations were modified with isotopic substitution. This analysis involved the statistical comparison of complimentary cumulative distribution functions (CDFs) derived from the PI data obtained for VR in KAP and DKAP at three temperatures (23 °C, 45 °C, and 60 °C) [ 116 ]. The results of this analysis are presented in Figure 10 .…”
Section: Photoluminescence Intermittency In Organic Luminophoresmentioning
confidence: 99%
“… Complimentary CDF’s of on -( a ) and off -( b ) event durations for VR in KAP and DKAP at all three temperatures [ 116 ]. Dashed lines are DKAP and solid lines are KAP at room temperature (blue), 45 °C (green), and 60 °C (red).…”
Section: Figurementioning
confidence: 99%
“…periods at the single particle level under continuous excitation. This phenomenon is not specific to nanocrystals, and has also been observed in molecular [11] and biological systems. [12] As a result, PL intermittency is characterized by dark 'off' states and bright 'on' states.…”
Section: Delayed Luminescence Kineticsmentioning
confidence: 70%